The Structure of Senior High School Mathematics Curriculum in Indonesia: A Focus on the Statistical Investigation and Reasoning - Yoga Dwi Windy Kusuma Ningtyas (JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study examines the structure of the intended curriculum in data analysis and probability within Indonesia's secondary mathematics curriculum. Through content analysis, the study breaks down the curriculum structure into three tiers: large, medium, and small. The analysis of the large structure indicates that the curriculum aligns with the goals of mathematics education, focusing on reasoning and problem-solving to enhance student numeracy at each stage. In the medium structure, the curriculum consistently employs a spiral model that aids student advancement from Level B to Level C, following the GAISE II framework. However, the small structure analysis uncovers a disproportion in the PPDAC investigation cycle, where the data, analysis, and conclusion stages overshadow the problem and plan stages. The study concludes that there is a need to reinforce the independent investigation planning stage in each phase to ensure that the shift from empirical to theoretical data is perceived as a coherent unit of statistical reasoning. Further research is suggested to assess the implemented and attained curricula.Keywords: intended curriculum, PPDAC, GAISE II, concept progression, statistical investigation, statistical reasoning